Definitions, interactions and beyond: response to Carlson, Galambos, Musselin and Wright. Issue 2 (3rd April 2018) - Galvez-Behar, Gabriel; Guagnini, Anna; Mercelis, Joris; Wadhwani, R. Daniel
ABSTRACT: Responding to the commentators on the two special issues (in Management and Organizational History and in History and Technology ) devoted to academic entrepreneurship in historical perspective, we renew our invitation to adopt a broad definition of the term entrepreneurship, and elaborate on our view that it can be a heuristically valid tool in the analysis of historical change in the academic, political, and social worlds. We agree, in particular, that more research needs to be carried out on the relationships between the institutional and commercial aspects of entrepreneurship in academia, and how the two aspects coalesced into forms of "organized entrepreneurship" at the university level. Particularly promising in this regard would be historical research on the interdependencies between entrepreneurial processes at the individual and organizational levels, the changing roles of administrative officers and governing bodies of institutions of higher education, and shifts in the regulation of academics' outside activities. Studies of the changing ways that business people and organizations integrate academic knowledge into products and enterprises in collaboration with academic partners would also contribute to this research agenda. For all the obstacles and difficulties arising from differences of interpretation across disciplines, interdisciplinary scholarship between history and the social sciences remains promising as a way to engage in research on the evolution of academic entrepreneurship, as well as an effective way to question the relevance of our concepts in our own disciplines.